The Timorese family and its cultural and administrative role in the twentieth century - د. ًازدار حنٔل وصطفّ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
in the first part of this research , is about the administration and culture rule of the Timur family in nineteenth century .especially the rule of scientist and writers .originally this family there grandfather name was muhammed timur kashf . he was lived in qalachwalan town , after the vanishing of that city and building suliymania city ,he went to Egypt and settled there until he died in Egypt.before he is travel to Egypt , he were had a good knowledge about the sciences he was a educated man ,after he arrive to Egypt, his made a strong friendship with muhammed ali pasha ,with most affairs of the kingdom he support muhammed ali pasha with his advice's , because of this he got many military positions and important administration positions . the rule of Timur family in twentieth century is the second part of the research , it consist of two part ,first part is , the created and the administration rule and the posts that he got it ,one of them (ahmed ismail muhammed kashf ) , he had got many important posts ,for example , he was member of elderly assembly of Egypt , he also was a member of board of knowledge in Eygept and syria ,another one of that family ( mahmmud ismail timur) because he was brilliant as a writer ,he got reward and he got many appreciation letter ,as a reward from qairo knowledge board , also we got appreciation from the state , the second part of the research is about , writing and publishing activity from the Timur family , before all of them the big writer of famillty muhammed ismail , he is the writer of many great books , for example ( the light of soul) , ( the edge) (the bird in cage) . and another scintist from this family ( muhammed ahmed ismail) also he had a great rule as a writer and thinker , his books ( salwa fe mahab reh) and ( kilopatra fe khan khalil) he also had books and traveling this book ( abul hawl flying ) whats important in history of this family , they were had a good rule in nineteenth and twentieth century in Egypt , the had rule as administrations and writers also as scientists , also by there great rules Egypt developed and and because of there great rules the became famous family in Egypt.